Elaphostrongylus and Dictyocaulus infections in Norwegian wild reindeer and red deer populations in relation to summer pasture altitude and climate. (December 2019) - Handeland, Kjell; Davidson, Rebecca K.; Viljugrein, Hildegunn; Mossing, Anders; Meisingset, Erling L.; Heum, Marianne; Strand, Olav; Isaksen, Ketil
Abstract: Nematodes of the genera Elaphostrongylus and Dictyocaulus are associated with disease in semi-domesticated tundra reindeer and farmed red deer whereas less knowledge exists in the wild. Their first stage larvae (L1) develop to the infective third stage (L3) in the environment; Elaphostrongylus spp. within intermediate gastropod hosts and Dictyocaulus spp. as free-living larvae. Larval development of Elaphostrongylus is highly temperature dependent with a developmental minimum of 9–10 °C. Larval development of Dictyocaulus spp. may occur at low temperatures (5 °C) but the larvae are sensitive to desiccation. We examined the prevalence and intensity of Elaphostrongylus spp. and Dictyocaulus spp. infections in six wild reindeer and two wild red deer populations in relation to altitude, temperature and rainfall in their respective main summer pasture area over the 5 summers prior to sampling. The parasitological examination was based upon morphological identification of L1 in the faeces of hunted animals. Altitude was calculated from animal position data and temperature and precipitation by means of a nationwide gridded data set. Temperature decreased with increasing altitude, from 13.3 °C for the lowest located red deer population (300 m) to 6.1 °C for the highest located reindeer population (1400 m). No significant relationship between altitude and rainfall was identified. Elaphostrongylus spp. infection decreased in prevalence with increasing altitude, being identified in 89% of investigated samples from the lowest located population and in 3% of samples from the highest. The prevalence of Dictyocaulus spp. infection varied between 28 and 80% and no relationship with altitude was found. The intensity of Elaphostrongylus spp. infection was low in reindeer and moderate in red deer whereas the intensity of Dictyocaulus spp. infection was moderate in both species. Our results indicated that the climatic conditions in all areas studied were suitable for Dictyocaulus spp., whereas summer temperature was a restrictive factor for Elaphostrongylus sp. in reindeer. Graphical abstract: Image 1 Highlights: 6 wild reindeer and 2 red deer populations investigated for nematode larvae. Elaphostrongylus spp. and Dictyocaulus spp. prevalence varied: 3–89% and 28–80%. Elaphostrongylus spp. prevalence decreased with increasing grazing altitude. No relationship between altitude and Dictyocaulus spp. prevalence. Summer temperature restrictive factor for Elaphostrongylus sp. in reindeer.